Effect of planting density and fertilization on yield and tuber characteristics of potato of Group Andigenum - Vásquez, Víctor; Huerta Fernández, Pablo; Cabrera Hoyos, Héctor Antonio; Jiménez, Luis; Pando Gómez, Rosmeri Veronica; Carranza, Víctor; Carranza, Cristian; Argomedo, Betzabé (Facultad de Agronomía, Universidad Nacional de Colombia, 2025)
Fertilization and planting density are important practices in potato-producing regions, particularly in regions where yields are not optimal. In addition, appropriate characteristics are required for industrial processing of potato, prompting farmers to improve their productivity and produce varieties demanded by the agroindustrial market. The aim of this study was to determine the effect of two planting densities: 0.20 m x 1.00 m (50,000 plants ha¹) and 0.40 m x 1.00 m (25,000 plants ha¹) and three NPK fertilization doses (60-60-60, 120-120-120, 180-180-180) on the yield and tuber characteristics of potato (Solanum tuberosum Group Andigenum) varieties Serranita, Luyanita, and Capiro. A randomized block design was used with subdivided plots and three replicates. The results indicate higher total yield and commercial yield (42.87 and 38.74 t ha¹) with the 180-180-180 kg ha¹ dose of NPK. The Luyanita variety stood out with yields of 36.03 and 30.97 t ha¹ of total and commercial tuber yield, respectively. The highest total and commercial tuber yields were obtained with the density 0.20 m x 1.00 m. The Luyanita variety showed acceptable physicochemical characteristics for agribusiness with 24.73% dry matter, low content of reducing sugars (0.21%), acceptable color of fries (3.11), specific gravity (1.11 g cm³) and adequate oil content (20.44%). The planting density factor showed no statistically significant differences.